An Inclusive Future for Assistive Technologies Supporting People with Visual Impairments: An Overview of Trends and Challenges - Kamil TROJNAR; Krzysztof TERESZKIEWICZ (Communications of International Proceedings, 2025)
This paper provides a comprehensive overview of current trends and persistent challenges related to the development of assistive technologies for people with visual impairments. The analysis focuses on the role of these technologies in increasing independence, digital accessibility and social participation. The motivation for addressing this topic is the dynamic development of digital innovations and the growing importance of inclusive design, which create both new opportunities and significant barriers for users with visual impairments. The paper is based on a review of scientific literature and institutional documents concerning the technological, social and ethical aspects of innovation in assistive technologies. The analysis highlights a consistent gap between research and practical implementation. Many solutions remain at the prototype stage, and their adoption is hindered by high costs, insufficient standardisation, limited training, and inadequate involvement of users in the development process. The findings demonstrate that the creation of an accessible ecosystem of assistive technologies requires interdisciplinary collaboration, supportive public policies, and the active participation of visually impaired people in co-design. The study concludes that the integration of technological innovation with social responsibility and coherent systemic support is essential for building an inclusive digital future. The results offer practical recommendations for designers, researchers, and policymakers who work towards improving digital accessibility at national and international levels.
Keywords: assistive technologies; visual impairments; accessibility; inclusive design